Leaf and branch extracts of Eriobotrya japonica exert antibacterial activity against ESBL-producing Escherichia coli and Klebsiella pneumoniae - Elias Abdou; Ziad Daoud; Abdel-Massih Roula (International Journal of Phytomedicine, 2011)
In this study, the antimicrobial activity of leaves and branches of Eriobotrya japonica, a Lebanese endegenious plant, against Extended Spectrum Beta Lactamase -producing Escherichia coli and Klebsiella pneumoniae was determined and the specific plant fraction responsible for this antimicrobial activity were identified. The plants were extracted with ethanol to yield the crude extract which was further subfractionated by different solvents to obtain the petroleum ether, the dichloromethane, the ethyl acetate and the aqueous fractions. The Minimum Inhibitory Concentrations (MIC) and Minimum Bactericidal Concentrations (MBC) were determined using broth microdilution. Both inhibitory and bactericidal effects of Eriobotrya japonica on Escherichia coli and Klebsiella pneumoniae were mainly observed with the crude extract of the plant, the ethyl acetate, the Dichloromethane, and the aqueous fractions. The antibacterial effect of the Petroleum ether fraction was limited with the leaf extract; however, it was acceptable with the branch extract. The lowest MIC90 was observed with ethyl acetate fraction for both leaf and branch extracts with Escherichia coli and Klebsiella pneumoniae. The concentrations at which most of strains were inhibited ranged between 40 μg/μl and 80 μg/μl. MICs and MBCs effects were detected within 1 dilution. This study constitutes a good example for the screening of antimicrobial activities of plants on highly resistant organisms of clinical importance; however, toxicity of these extracts needs more investigation.